An Analysis on Effectiveness of Compensation Planning: HR Policy: Examining the Impact of Compensation Planning on Employee Retention and Commitment (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Compensation policy is a thought that is getting progressively tested to draw in and hold employees in the present tight activity market. The Compensation policy ought to what's more envelop both fiscal and non-financial prizes paid to worker in return of the administrations rendered while thinking about business agreement, capability and abilities. This paper planned for setting up the impact of pay strategy on employee responsibility.